Parenting self-efficacy instruments for parents of infants and toddlers: A review - Meenakshi Seetharaman; Annella Benjamin; Jacqueline M. McGrath; Ashlee J. Vance (Elsevier, 2022)
Background: Parenting Self-Efficacy, a concept first described in Bandura's Social Cognitive Theory, is a parent's belief in their ability to successfully parent their child. The concept of parenting self-efficacy is used by researchers to increase our understanding of parenting abilities and influences on child health and developmental outcomes. Numerous instruments exist for measuring parental self-efficacy; but little is known about the specific topics included in the measures and consistency across instruments. Therefore, this scoping review sought to compare parenting self-efficacy instruments for parents of infants and toddlers, focusing on comparison of parenting topics, scale format, and administration with the goal of providing guidance and recommendations for measurement selection. Methods: Our sample included 25 instruments and items from every instrument was evaluated and coded using NVIVO Qualitative Software. We reviewed the instruments' target population, subscales, number of items, response options, scoring range and instructions, theoretical background, and parenting topics across each instrument. Results: This review found three common factors across all instruments: parent, social and family, and child factors. Parent personal factors were addressed most frequently to evaluate self-efficacy and included topics such as, perception of parenting abilities, emotional reactions, and perceived successes. From our synthesis, we also offer recommendations for instrument selection and provide a conceptual model of parenting self-efficacy. Conclusions: The findings from this scoping review highlight the presence of key factors (parent, social & family, and child) necessary for the evaluation of parenting self-efficacy in parents of infants and toddlers. Given our results, a meta-analysis is needed to compare parenting self-efficacy scores across studies to better understand the associations between self-efficacy and parent and child outcomes.